Internal communication in the partners of a market in the Central Highlands of Peru - Cabrera Vega, Arón Orlando (2020)
The objective of the investigation was to characterize the internal communication in the partners of the Ramos Toscano Market in Huancayo - Peru. The study was of mixed approach, basic type and simple descriptive design, in the quantitative stage a sample of 110 market partners was obtained, to whom an internal communication questionnaire designed for the investigation was administered, and in the qualitative stage counted with a sample of 5 market partners to whom in-depth interviews were conducted. As a result, it was found that the level of internal communication in the Ramos Toscano Market is high (66.4%), prevailing non-formal communication channels and spontaneous communication modes that enable efficient organization, especially when the objectives are common. It was concluded that internal communication in the analysis unit is high, mainly due to the length of employment of the members, generating a coexistence that allows adequate communication, predominantly non-formal, direct, horizontal, spontaneous and empowered by respect for values of the Andean peoples as solidarity and cooperativism.